Spectral filtering experimentation on photovoltaic cells using novel bio-filter made from copper coated hibiscus-ethanol extract - Moses E. Emetere; Testimony Gabe-Oji; Durodola B.M. (Institute of Advanced Engineering and Science, 2020)
The challenges facing solar power grid system in Africa is huge. Most salient of these challenges is the inefficiency of the photovoltaic (PV) panel to sustain its output for more than a year. Certainly, the harsh weather condition in the region can be said to be one of the reasons for the shortcoming that was earlier highlighted. In this research, bio-filters were suggested to filter the harmful radiation hitting the PV panel. The bio-filter is made up of copper coated hibiscus extract. The hibiscus extract was done using ethanol solution. It was observed that the bio-filter was able to filter the some of the harmful radiation as expected. The quantity of the harmful solar radiation was not estimated because of the limitations of the equipment used for the research. It is recommended that this highlighted shortcoming of the research should be taken further to ascertain i.e. in percentage the harmful radiation that has been filtered by the bio-filter during the experiment.